INVESTOR PERCEPTION OF CORPORATE DISCLOSURE AND ITS INFLUENCE ON INVESTMENT DECISIONS IN INDIA - Durge, Nishad Rajratna; Khapane, Vinod S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate disclosure is critical towards informed investment decisions by mitigating on information asymmetry, and increasing transparency between firms and investors. The empirical research allows investigating how Indian investors regard the corporate disclosure practices, as well as to what degree these disclosures affect their investment decisions. The study based on descriptive research design and survey data collection of 200 investors of various categories in the Indian capital market discloses that most of the investors are moderately or highly aware of the corporate disclosure norms and use financial statements, annual reports, and stock exchange filing substantially to make investment decisions. Although the financial performance metrics are still the most favored form of disclosure, the significance of non-financial disclosures, including governance practices and sustainability reports are slowly rising. The research points out at the importance of more convenient, understandable and investor-friendly disclosure forms. On the basis of these findings, the paper presents practical suggestions to corporates, regulators, and financial advisors, regarding facilitation of the overall efficacy of disclosure practices in India. The study adds to the extant literature in the field by providing information on the behavioural reaction of Indian investors to corporate transparency and recommending prospective avenues of enhancing corporate-investor communication.